PENGARUH LOAN TO DEPOSIT RATIO (LDR) DAN CAPITAL ADEQUACY RATIO (CAR) TERHADAP RETURN ON ASSETS (ROA) PADA PT BANK MEGA TBK PERIODE 2012-2023 - Aryani Wahyudi, Devi; Dwi Nugroho, Riski (Journal of Research and Publication Innovation, 2024)
This research aims to determine whether there is an influence of the Loan to Deposit Ratio and Capital Adequacy Ratio on Return on Assets at PT Bank Mega Tbk for the 2012-2023 period. This research is a descriptive analysis study with a quantitative approach. The population in this study is the financial report of PT Bank Mega Tbk for 2012-2023. The research samples used are the Balance Sheet Report, Profit and Loss Report, and Notes to the Company's Financial Reports. The analysis in this study used the SPSS Version 26 software program. The statistical method used was multiple regression analysis, classic assumption tests (normality test, multicollinearity test, autocorrelation test, heteroscedasticity test), coefficient of determination test (R2) and hypothesis testing (t test and t test). f). The research results on the Loan to Deposit Ratio (X1) variable show that there is no influence on Return on Assets, seen from the t test (partial test) which shows the value of tcount ≤ ttable (0.597≤ 2.262) which is significant 0.565 ≥ 0.05. The Capital Adequacy Ratio (X2) variable shows that there is a partial positive influence, seen from tcount ≥ ttable (3.225 ≥ 2.262) which is significant 0.010 ≤ 0.05. Simultaneous results show that there is an influence between Loan to Deposit Ratio and Capital Adequacy Ratio on Return on Assets as seen from the results of the F test (simultaneous test) which shows Fcount ≥ Ftable (6.051≥4.10). The results of the determination test show an Adjusted R square value of 0.479, meaning that the influence of the Loan to Deposit Ratio and Capital Adequacy Ratio on Return on Assets at PT Bank Mega Tbk Company for the 2012-2023 period is 47,9% and the remaining 52.1% is influenced by other variables outside this research.